2012
DOI: 10.1519/jsc.0b013e3182281c87
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Training at the Same Time of Day and Tapering Period on the Diurnal Variation of Short Exercise Performances

Abstract: The purpose of this investigation was to assess the effects of training and tapering at the same time of the day on the diurnal variations of short exercise performances. Thirty-one physically active men underwent 12 weeks of lower-extremity resistance training and 2 weeks of tapering. These subjects were matched and randomly assigned to a morning training group (MTG, training times 0700-0800 hours, n = 10), an evening training group (ETG, training times 1700-1800 hours, n = 11), and a control group (CG, compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
47
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 24 publications
7
47
1
2
Order By: Relevance
“…For the elite athlete, behaviours such as sleep as well as daytime activities are often dictated by training and competition schedules (Sargent et al, 2014). In circumstances where athletes are required to perform at a different time of day, performance adaptations can occur when training programs are carried out at the time of day at which their upcoming competition will take place (Chtourou et al, 2012; Hill et al, 1989; Souissi et al, 2002). Chtourou et al (2012) confirmed that exercise training modified the diurnal variations of performance with greater improvement in performance at the time of day at which training was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…For the elite athlete, behaviours such as sleep as well as daytime activities are often dictated by training and competition schedules (Sargent et al, 2014). In circumstances where athletes are required to perform at a different time of day, performance adaptations can occur when training programs are carried out at the time of day at which their upcoming competition will take place (Chtourou et al, 2012; Hill et al, 1989; Souissi et al, 2002). Chtourou et al (2012) confirmed that exercise training modified the diurnal variations of performance with greater improvement in performance at the time of day at which training was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Diurnal variation of cognitive performance and perceived difficulty in dart-throwing performance in 9-10-year-old boys Introduction Various psychological and physiological functions have been shown to undergo changes relative to the time of the solar day (Atkinson & Reilly 1996;Chtourou et al 2012). These variations are known as circadian or diurnal rhythms (Cappaert 1999;Chtourou et al 2012).…”
mentioning
confidence: 99%
“…These variations are known as circadian or diurnal rhythms (Cappaert 1999;Chtourou et al 2012). Circadian rhythms are present in several elements of sensorimotor, psychomotor, perceptual, and cognitive function (Jarraya et al 2013;Jarraya, Jarraya, Chtourou, et al 2014).…”
mentioning
confidence: 99%
“…Possible approaches have included a reduction of food and fluid intake, exercising in impermeable plastic blouses and suits to increase sweating, and passive dehydration (sitting in a sauna) [8, 21]. Often, endurance exercise is added to the usual training sessions; this supplementary exercise reduces body mass, but the need to increase training volume/load negates efforts at tapering, and it may result in fatigue, overreaching, or overtraining, with negative effects on mood and physical performance [22]. More aggressive and prohibited tactics include self-induced vomiting and the use of diuretics, laxatives, and anorexic medication [8, 19].…”
Section: Overviewmentioning
confidence: 99%